Trade interaction between India and ASEAN countries: an empirical study - Philip, Abey; Alapppatt, M. (Inderscience Publishers, 2015)
This paper investigates the importance of relevant macro variables of trade between ASEAN countries and India. It is also important to analyse the significance of different bilateral agreements and its impact on Indian international trade. GATT and WTO have been advocating trade liberalisation and bilateral agreement and aims to promote free trade among the member countries. This paper tries to look into India’s market led regional interaction among ASEAN countries. The national saving of ASEAN countries and free trade agreement seems to be influencing the bilateral trade of India. The study shows that increase in national saving helps ASEAN countries to mobilise their investment opportunity to India. Increase in inflation may lead to appreciation of ASEAN currency compared to Indian and it negatively influences the international trade in India. More importantly, the study found out that distance significantly influences the international trade and it means that still we are far away the concept of the global village. The study depicts that free trade agreement promotes the international trade and it helps countries to reduce their indirect costs. This paper will help the policy makers to understand how much international trade and involvement in bilateral agreement is helping India to become an important role player in Asia.